Dialektika Arsitektur dan Teknologi Islam Nusantara: Pengaruh Budaya Lokal dan Nilai-nilai Islam - Habibi Zaman Riawan Ahmad (Refleksi: Jurnal Kajian Agama dan Filsafat, 2023)
This article describes cultural acculturation in Islamic architecture and technology in Nusantara. Cultural acculturation in the architectural aspect is limited to two mosques of the early Islamic era in Nusantara, namely the Great Mosque of Demak and the Gedhe Mosque of Yogyakarta Palace. The cultural acculturation of mosque construction is reflected in the main building, the portico, and the supporting elements of the building, as well as the meaning of symbols and ornamens. The meaning of symbols and ornamens explains the strong acculturation of local culture with Islamic values. Specifically on the technological aspect, this article examines the naval and cannon technology of the Islamic era of Demak and later sultanates. The article concludes that the entry of Islam into Nusantara created a struggle between Islam and the local culture, which was influenced by Hinduism, Buddhism, and cults, as well as the original values of the archipelago, which are reflected in the construction of buildings and war equipment.